EFFECT OF JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT TO TURNOVER INTENTION AT PT. ACS AEROFOOD - Lukman Nuzul Hakim; Muh Abd Rosid; Indah Kusumawati (Bajang Institute, 2022)
This study aims to analyze the effect of Work and Organizational Commitment on Turnover Intention at PT. Aerofood ACS. The sample of this research is 97 respondents of employees of PT. Aerofood ACS with a population of 2,749. The method used is a quantitative method. The collection of primary data obtained from the distribution of questionnaires and secondary data obtained from the company. The analytical technique used is multiple linear regression analysis using SPSS version 24 software. The results showed that partially the work objective variable (X1) did not have a positive effect on Turnover Intention (Y). This is indicated by tcount < t table ie 1.395 < 1.661, Organizational Commitment (X2) has a positive effect on Turnover Intention (Y). This is indicated by t arithmetic > t table which is 4.513 > 1.661 and a significant regression value of 0.000 is smaller than 0.050. Simultaneously the work variable (X1) and Organizational Commitment (X2) have a positive effect on Turnover Intention (Y), namely Fcount > Ftable of 31,223 > 2,70. With multiple regression equation value Y = 6.908 + 0.247X1 + 0.618X2 with a coefficient of determination of 39.90% which is influenced by factors not examined.